Wrist strap type medical terminal - GONG YUHUAN; MO YUCHANG (2018)
The invention discloses a wrist strap type medical terminal. The wrist strap type medical terminal is characterized in that five notches for mounting wearable monitors are formed in the side surfacesof a wrist strap, first U-shaped grooves are formed in the lower sides of the left side wall and the right side wall of the first notch and are used for fixedly mounting the blood oxygen monitor, first protrusions are symmetrically arranged on the left side and the right side of the second notch and are used for providing sufficient heat dissipation spaces to the electrocardiogram monitor mountedin the second notch, second U-shaped grooves are symmetrically formed in the left side and the right side of the third notch and are used for fixedly mounting the blood pressure monitor, springs are arranged on the right side of the fourth notch and are used for cushioning the body temperature monitor mounted inside the fourth notch, and slopes are arranged on the lower right side of the fifth notch and are used for positi